Ergonomic evaluation of passive lower-limb exoskeletons in simulated industrial tasks at non-optimal workstations. - Ardiyanto, Ardiyanto; Nazar, Muhammad Rama; Ramadhan, Rachmad Falah; Putera, Dewa Ngurah Mahaswara; Herawati, Dian; Herianto, Herianto (Work, 2026)
Background: Industrial tasks often require workers to maintain awkward static postures at non-optimal workstations, leading to physical strain and musculoskeletal issues. Exoskeletons offer potential ergonomic benefits by reducing physical workload. However, the efficacy of passive lower-limb exoskeletons in non-optimal workstation conditions remains unclear. Objectives: This study examines the ergonomic efficacy of a passive lower-limb exoskeleton during simulated industrial tasks performed at workstations with varying heights and tilt angles. Methods: Sixteen participants performed bolting tasks at workstations configured at two heights (60 cm and 90 cm) and three tilt angles (0°, 45°, and 90°), under exoskeleton and non-exoskeleton conditions. Assessments included muscle activity (erector spinae and rectus femoris), joint angles (lumbar, hips, and knees), segmental REBA scores, perceived exertion, and perceived discomfort. Mixed-effects and generalized linear mixed models evaluated the impact of workstation conditions and exoskeleton use. Results: The exoskeleton reduced erector spinae muscle activity by an average of 39% and supported more neutral hip and knee postures (p < 0.001), though it increased rectus femoris activity at the higher workstation (p < 0.001) and segmental REBA scores for the trunk and leg under specific conditions (p < 0.001). Furthermore, although exoskeleton use did not have a significant effect on perceived exertion or discomfort, workstation height significantly influenced both variables (p < 0.001 and p < 0.05, respectively). Conclusions: The passive lower-limb exoskeleton may reduce specific muscle loads and improve posture in non-ideal settings, though its efficacy varies by workstation configuration.